A Numerical Algorithm for Nuclear Reaction in Deuterium-Tritium Plasma. (19th May 2019) - Pan, Dongmei; Zhao, Zijia; Chen, Zhong; Lv, Zhongliang; Li, Junhan
Abstract: Rates of neutron production in deuterium-tritium (D-T) plasmas below the temperature of 100 keV have been widely studied with analytical cross sections based on nuclear physics. In the present work, a new algorithm of numerical simulation using the latest nuclear database ENDF/B-VII, discrete ordinate (SN ) method, and Monte Carlo methods was developed to describe nuclear reactions in D-T plasma. Compared with the method that used analytical cross section, this new method can predict the nuclear reaction in plasma to several hundreds of kilo-electron-volts and has the potential to give information about directionality of the neutron flux and other interesting nuclear reactions, if needed.